Ornament on the Pendhok of the Surakarta Kris - Guntur - (Institut Seni Indonesia Denpasar, 2018)
The type of ornament found on the Javanese kris pendhok is rarely discussed from an iconographic point of view. The pendhok is the decorative protection plating found on the sheath of the kris, usually made from metals such as silver, bronze, copper, brass, and even gold. The kris is a Javanese dagger. This essay focuses on the pendok ornament of the Surakarta kris, and on its symbolism. The pendhok is a ‘patronage’ art, traditionally manufactured by palace’s mranggi-s(the sheath maker), and today by kris craftsmen. Its various motifs–vegetation, plants, animals, or other motifs–are combined with lung-lungan (curly, vegetation-looking forms) in such a way as to create symmetric-vertical ornaments. The lung-lungan and alas-alasan (the forest as cosmos) motifs are more numerous than flora, wayang puppets, and geometrical motifs. The designs emphasize symmetry, repetition and harmony as their basic principle. The ornament style is believed to embody the ‘syncretic-mystique’ of Javanese Islam. The ornaments embossed on the surface usually refer to pre-Islamic, Hindu-Buddha notions.Ornamen pendhok keris sebagai ikonografi Jawa jarang dibahas. Pendhok adalah lapisan dekoratif pelindung keris, yang biasanya terbuat dari berbagai logam seperti perak, perunggu, tembaga, kuningan, dan bahkan emas. Keris adalah jenis senjata tusuk Jawa. Artikel ini difokuskan pada hiasan pendhok dari keris Surakarta, dan simbolismenya dalam pencitraan Jawa. Pada awalnya, ornamen pendhok adalah seni ‘patron’, yang dibuat oleh mranggi istana (pembuat sarung), dan saat ini ‘diciptakan kembali’ oleh para pembuat keris di banyak tempat. Motif bunga, tanaman, hewan, atau figural pada pendhok, adalah komposisi dan penggabungan dengan lung-lungan (penggayaan tanaman) sebagai cara untuk membentuk irama ornamen secara simetris-vertikal, ornamen disederhanakan sebagai lung-lungan. Motif lung-lungan dan alas-alasan (kosmos hutan dalam imajinasi spiritual), mendominasi gaya ornamen dibandingkan dengan motif lain seperti tanaman/flora, wayang (boneka), dan geometri. Komposisi simetri, repetitif, dan harmoni menjadi yang paling ‘prinsip’ pada desain. Gaya ornamen diyakini melambangkan ‘sinkretis-mistik’ dari Jawa - Islam, ornamen yang ‘timbul’ pada permukaan yang berdimensi, menjadi ekspresi relief, yang sebagian besar menandakan seni yang diadopsi pra-Islam: Hindu – Buddha